DAMPAK NEGATIF GAME ONLINE TERHADAP MINAT BELAJAR SISWA KELAS V SD NEGERI 0105 SIBUHUAN - Riski Hamdan Syahputra; Harahap, Nurhalimah; Daulay, Muhammad Sukril (Journal Education Innovation (JEI), 2025)
The objectives in this study were (1) to determine the negative impact of online games on the interest in learning of fifth grade students of SD Negeri 0105 Sibuhuan. (2) To find out the strategy to overcome the negative impact of online games on the interest in learning of fifth grade students of SD Negeri 0105 Sibuhuan. This research is qualitative research. The research was conducted at SD Negeri 0105 Sibuhuan. The subjects of this research are Class V Teachers, and Class V Students. Data collection techniques were carried out using observation, interviews and documentation. Activities in qualitative data analysis use interactive models, namely data collection, data reduction (reduction), data presentation (display), and conclusion drawing. Based on the results of the study, it shows that 1. the negative impact of online games is to make excessive addiction, make eyes damaged, make lazy, make not concentrate, sleep less and lie. 2. efforts in overcoming the negative impact of online games on the learning interest of fifth grade students of SD Negeri 0105 Sibuhuan are by reducing the level of smart phone usage, by supervising children when playing online games, by telling children to do useful activities, by giving advice and understanding of online game play and by instilling religious values to children.